2019
DOI: 10.18632/aging.102254
|View full text |Cite
|
Sign up to set email alerts
|

HnRNPR-CCNB1/CENPF axis contributes to gastric cancer proliferation and metastasis

Abstract: Gastric cancer (GC) is a common disease globally with high mortality rate. It is therefore necessary to develop novel therapies targeting specific events in the pathogenesis of GC. Some hnRNP family members are involved in multiple cancer biological behaviors. However, the potential function and mechanism of hnRNPR, a new molecule of hnRNP family in GC remains unknown. We found that the expression of hnRNPR was significantly overexpressed in multiple cancers compared to the normal tissues. Functionally, hnRNPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 41 publications
2
62
0
Order By: Relevance
“…To date, there is no reported functional role of CENPF implicated in CC. However, CENPF was reported to be overexpressed, drive tumorigenesis and/or associated with poor prognosis in several human malignancies, including breast cancer [40], prostate cancer [41][42][43][44], bladder cancer [45], gastric cancer [46], hepatocellular carcinoma [47][48][49], pancreatic carcinoma [50]. In this study, higher CENPF expression was found to be significantly associated with metastasis compared to CC tissues (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…To date, there is no reported functional role of CENPF implicated in CC. However, CENPF was reported to be overexpressed, drive tumorigenesis and/or associated with poor prognosis in several human malignancies, including breast cancer [40], prostate cancer [41][42][43][44], bladder cancer [45], gastric cancer [46], hepatocellular carcinoma [47][48][49], pancreatic carcinoma [50]. In this study, higher CENPF expression was found to be significantly associated with metastasis compared to CC tissues (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Small molecule compounds targeting CENPF have not been reported, possibly attributed by the difficulty to target a non-enzyme target. However, reports have shown that silencing CENPF using in vitro models abolished invasion in gastric cancer [46], resulted in the cell cycle arrest at G2/M checkpoint in hepatocellular carcinoma [47], reduced levels of epithelialmesenchymal transition markers, inhibited cell proliferation, migration, and invasion, reduced global bioenergetic capacity and altered the global metabolic profiles in prostate cancer [43,53]. It remained to be validated whether silencing/inhibiting either CENPF or both CENPF and TOP2A will have a strong phenotypic consequence in CC using an in-vitro or/and in vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, MCM3AP-AS1 could hasten tumor growth in breast cancer by targeting CENPF via competitively binding to miR-28-5p 17 . Besides, overexpression of hnRNPR promoted the aggressiveness of gastric cancer by increasing the mRNA expression of CCNB1 and CENPF 18 . Maybe the molecular mechanisms underlying the effects of CENPF on the oncogenesis of LUAD also could be regulated by noncoding RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all patients could benefit from anti-HER2 or anti-VEGFR monoclonal antibody and the monoclonal antibodies are not suitable for GC patients with negative HER2 or VEGFR expression [12]. Therefore, it is imperative to further elucidate the molecular mechanisms underlying GC invasion and metastasis fully so as to identify novel effective therapeutic targets [13].…”
Section: Introductionmentioning
confidence: 99%